Muatan Konten Lokal pada Materi Pelajaran Bahasa Inggris di SMP Negeri 5 Sigi - Herlina (Paedagogia: Jurnal Pendidikan, 2018)
Based on the 2013 curriculum 2016’s revision, there are subject materials that demand about local content in English subjects at the level of SMP Class VII. Teachers need many researches and practices integrating and implementating these subjects. Basically, it needs to be done in-depth study in the form of content analysis. This research was conducted on content and learning English in SMP Negeri 5 Sigi. This study aims to find out 1) how many percentage of local content in English lesson material Class VII SMP in the curriculum 2013 revision 2016; 2) how to integrate local content in English subject matter in SMP Negeri 5 Sigi; 3) how the implementation of material with local content in English learning in SMP Negeri 5 Sigi, and; 4) how to integrate local content in effective and efficient English lessons in SMP Negeri 5 Sigi. The study used a qualitative descriptive approach with the method of collecting document studies, interviews, and observation. The research results are 1) the proportion of local content that can be integrated into English language learning material SMP is 95%; 2) the integrity of local content in English learning materials in SMP Negeri 5 Sigi can be found in the lesson plan; 3) implementation of materials with local content in English learning attached to KTSP, Syllabus, lesson plan and learning resources enrichment book.